2013
DOI: 10.1007/s13193-013-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Thymic Tumors

Abstract: Thymic tumors represent 0.2-1.5 % of all malignancies with an incidence of 0.15 per 100,000 population. Thymic tumors are most common tumors of the anterior mediastinum accounting for 20 % of all mediastinal tumors and 50 % of all anterior mediastinal tumors. Over 90 % of all thymic tumors occur in anterior mediastinum, remainder occurring in neck or other mediastinal areas especially aortopulmonary window and retro cardiac area which are common sites for ectopic thymic tissues and possible explanation for fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…[10] The population described in this article was mainly masculine, unlike what was reported in the CLICaP-LATimus and the INC studies, were the proportion was inverted (40% men and 60% woman). [9,10] However, the mean age (52.7 years) was similar to the previous studies, unlike what has been reported in international cohorts, such as the European RARECAREnet projects (2000-20007) [11] or the Japanese publication by Kanemura et al, [12] in which patients were on average a decade older at diagnosis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[10] The population described in this article was mainly masculine, unlike what was reported in the CLICaP-LATimus and the INC studies, were the proportion was inverted (40% men and 60% woman). [9,10] However, the mean age (52.7 years) was similar to the previous studies, unlike what has been reported in international cohorts, such as the European RARECAREnet projects (2000-20007) [11] or the Japanese publication by Kanemura et al, [12] in which patients were on average a decade older at diagnosis.…”
Section: Discussionsupporting
confidence: 79%
“…As reported in the literature worldwide, the frequency of thymic tumors in both Latin America and Colombia is low; in fact, only 105 patients with thymomas were included in the multicenter study CLICaP-LATimus, [9] which was carried out from 1997 to 2018 in 7 Latin American countries (Mexico, Costa Rica, Colombia, Ecuador, Brazil, Peru and Argentina). In Colombia, a recent publication by Buitrago et al reported 31 patients with thymic tumors who were treated at the National Institute of Cancerology (INC) between 2006 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Although, thymomas are the most common adult tumors in the anterior mediastinal compartment, it is a rare neoplasm with an overall incidence of 0.13 cases per 100,000 individuals per year (13)(14)(15). A recent study based on a large cohort of patients with thymomas revealed that the 10-year OS rate was 0.73 (95% confidence interval 0.69-0.75) (16).…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] According to the International Thymic Malignancy Interest Group, complete resection can only be achieved by removing the whole thymus and surrounding tissue. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%